Wolf Music: Style, Context, and Authenticity in R. Murray Schafer's And Wolf Shall Inherit the Moon - Waterman, Ellen (Canadian University Music Review / Revue de musique des universités canadiennes, 1998)
R. Murray Schafer's environmental music functions as a model for his ideal of an authentic Canadian musical identity. Schafer's idea of the North is embodied both in the music's style and in its context. Three works from the music drama Patria the Epilogue: And Wolf Shall Inherit the Moon serve as examples of the influence of the northern soundscape on Schafer's musical style.